Woodpeckers : drilling holes and bagging bugs - Collard, Sneed B. (Bucking Horse Books, 2018)
If you see a bird standing on the side of a tree banging its beak against the trunk, chances are you're watching a woodpecker. Woodpeckers not only dazzle us with their good looks and personality, they exhibit some of the most interesting behaviors in the animal world. Explore this dynamic, exciting group of birds with award-winning children's science writer Sneed B. Collard III. Discover what scientists have learned about woodpeckers, why woodpeckers drill into trees, and the best way to serve ants at your next sleep-over. Be forewarned: the more you read, the faster woodpeckers will peck their way into your imagination! --dust jacket.